An analysis of ChatGPT generative content usage towards students’ academic work based on gender perspective - Nurfajri Ningsih; Sukristiningsih; Patur Rahman (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The rapid adoption of generative artificial intelligence (AI), particularly ChatGPT, has transformed students’ academic practices, raising important questions regarding usage patterns, academic integrity, and learning behavior. This study aims to examine gender-based differences in the frequency of ChatGPT usage among university students and to identify which academic tasks show the most significant variation between male and female students. A quantitative survey design was employed, involving 20 English education students from Institut Parahikma Indonesia and UIN Alauddin Makassar, consisting of 10 male and 10 female participants. Data were collected through a structured Likert-scale questionnaire and analyzed using descriptive statistics and comparative analysis to identify usage trends and behavioral patterns. The findings reveal that female students consistently demonstrate higher usage of ChatGPT across a wider range of academic functions, particularly in grammar improvement, understanding assignment instructions, and refining academic writing. In contrast, male students tend to use ChatGPT more selectively, mainly for comparing outputs and evaluating argument clarity. Both groups show low dependence on ChatGPT for full task automation, indicating maintained academic autonomy. The most significant gender-based difference is found in language enhancement tasks, where female students exhibit substantially higher engagement. These findings suggest that educators should consider gender-based preferences when integrating AI into learning environments and promote balanced, ethical, and critical use of generative AI to support effective and responsible academic practices